ชีวภัณฑ์อารักขาพืชสูตรใหม่ชนิดผงผสมน้ำ ที่ผลิตระดับอุตสาหกรรม เพื่อใช้ควบคุมโรคแคงเกอร์ของมะนาว ภายใต้สภาพแปลงเกษตรขนาดใหญ่ - ปรโลกานนท์ พงศธร; อธินุวัฒน์ ดุสิต; บุณณดากุล จตุพร (Thai Journal of Science and Technology, 2018)
Abstract Two of thirty-three strains of antagonistic bacteria collected from organic lime plant rhizosphere were characterized. Strains TU-Orga13 and TU-Orga14 were significantly (P = 0.05) high accumulation of salicylic acid within lime plant with 0.714 and 0.689 mg/g fresh weight, respectively, after seed treatments with each strain (1 x 108 cfu/ml) ratio 10 ml/ 1 kg seed when compared to other strains and controls. Those two strains also showed the biggest clear zone of Xanthomonas axonopodis pv. citri, the causal agent of canker on lime plant, inhibition with 2.00 and 1.93 cm, respectively, when compared to other strains and controls which investigated by agar diffusion. The development of novel wettable powder biopesticides containing carriers, additives and biocontrol agent strains TU-Orga13 and TU-Orga14 in six formulations under pilot scale production, biochar-carrier based was established. A biochar-based formulation 3, Formula 3 [biochar, talcum, dolomite, calcium carbonate, CMC, and soybean extract mixed with TU-Orga13 (1016 cfu/ml) ratio 10 ml: 500 g of bioformula] showed the highest survival cells of TU-Orga13 with 2.8 x 1016, 2.8 x 1015, 1.9 x 1013, and 2.8 x 1010 cfu/g of biopesticide at 1, 3, 6, and 12 month-storages, respectively. Subsequently, Formula 3 significantly reduced the number of canker on lime plant leaves and significantly reduced the number of X. axonopodis pv. citri on lime plant leaves after soil drenched ratio 50 g/ 20 L. of water in total volume 300 ml/plant under greenhouse conditions with 5.00 sores and 1.13 x 106 cfu/g fresh weight, respectively. Moreover, Formula 3 showed the highest accumulation of salicylic acid within 24 h after challenged inoculation with X. axonopodis pv. citri with 0.624 mg/g fresh weight. Moreover, lime plant treated with Formula 3 soil drenched as mentioned above showed the highest accumulation of salicylic acid within 10 days when compared to other formulas and controls under greenhouse conditions. In the same trend, Formula 3 biopesticide, 1, 3, 6, and 12 month-storages, soil drenched significantly reduced the number of canker on lime plant leaves with 5.33, 5.67, 6.00 and 7.00 sores, respectively that correlated with X. axonopodis pv. citri population on leaves with 1.12-1.28 x 108 cfu/g fresh weight and the highest accumulation of salicylic acid within 24 h after challenged inoculation with X. axonopodis pv. citri with 0.654, 0.450, 0.440 and 0.429 mg/g fresh weight, respectively under farmer field conditions. Identification of TU-Orga13 by standard methodology of morphological, biochemical and molecular levels was showed 100 % similarity of Bacillus subtilis. This study indicated that Bacillus subtilis TU-Orga13 in novel Formula 3 quickly expressed the secretion of secondary metabolites and salicylic acid within lime plant against X. axonopodis pv. citri. Keywords: organic agriculture; biochar; biological control; plant pathogenic bacteria; salicylic acid